2016
DOI: 10.1098/rsbl.2016.0490
|View full text |Cite
|
Sign up to set email alerts
|

Early diving behaviour in juvenile penguins: improvement or selection processes

Abstract: The early life stage of long-lived species is critical to the viability of population, but is poorly understood. Longitudinal studies are needed to test whether juveniles are less efficient foragers than adults as has been hypothesized. We measured changes in the diving behaviour of 17 one-year-old king penguins Aptenodytes patagonicus at Crozet Islands (subantartic archipelago) during their first months at sea, using miniaturized tags that transmitted diving activity in real time. We also equipped five non-br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 12 publications
(25 reference statements)
1
62
0
Order By: Relevance
“…Orgeret et al (2016) showed that juvenile king penguins from the same colony move over considerable distances during their first year at sea, with probable changes in T w . In our calculations concerning heat loss, we assumed a T w of 4°C (Guinet et al, 1997;Charrassin and Bost, 2001), while birds might have foraged in somewhat colder water.…”
Section: Concurrent Changes In Dive Effort And/or Changes In T Wmentioning
confidence: 99%
See 4 more Smart Citations
“…Orgeret et al (2016) showed that juvenile king penguins from the same colony move over considerable distances during their first year at sea, with probable changes in T w . In our calculations concerning heat loss, we assumed a T w of 4°C (Guinet et al, 1997;Charrassin and Bost, 2001), while birds might have foraged in somewhat colder water.…”
Section: Concurrent Changes In Dive Effort And/or Changes In T Wmentioning
confidence: 99%
“…While juvenile birds remained at sea for their entire first year (apart from brief periods spent on land or ice), adult breeders repeatedly switched between foraging at sea and fasting in the colony, changing the overall dynamics of their body condition/insulation and, consequently, peripheral temperatures at sea. Orgeret et al (2016), who deployed satellite tags on 17 juvenile king penguins from the same Crozet colony during their first year at sea, found that dive performance (dive depth and duration) in 5 of these birds started to decline significantly after ∼3 months and satellite transmission stopped after ∼4 months, when these birds presumably died. The authors attributed this outcome to the inability of these birds to increase their dive capacity (as surviving birds did) when conditions became difficult, resulting in early mortality due to starvation (Orgeret et al, 2016).…”
Section: Seasonal Changes In Body Condition and Insulation Statusmentioning
confidence: 99%
See 3 more Smart Citations